A Modified Non Electrical Filter for Decontamination of Iron Rich Water for Rural Application - Umlong, Iohborlang M; Dutta, Dhiraj; Dubey, Rama; Dwivedi, Sanjai K. (Defence Life Science Journal, 2022)
A non-electrical filter is designed to cater the need of providing iron free water in forward and rural areas. The features of the unit are equipped with the aeration system and activated sand chemically coated by iron oxide as catalytic and filtering media which can bring down iron concentration from 12 mg/L to desirable limit. It increases the pH of water from acidic to pH above 7. This is in contrast to some indigenous water filter which existed in the North Eastern India that tend to remove iron below 4 mg/L. The modified filter is effective in reducing excess total dissolved solids (TDS) from drinking water. All other physical parameters found to be within the prescribed limit. It can give iron free water with output capacity of 25L/hr. The added advantage of the unit is the provision for back washing of the filter media and collection point of the precipitated iron at the lower bottom of the tank for safe discharge.